Study of some physical properties of bismuth doped borate glass - Ghanem, A. H.; Gaballah, N. (IJRDO-Journal of Applied Science, 2016)
Glass samples of the formula (70-x) B2O3 -xBi2O3-15Zn-15Na2O have been prepared by the melting quenching technique. The structural and optical characterisations of the glassy system were carried out by XRD, density, molar volume and FTIR technique. The powder X- ray diffraction of the prepared glass confirms the amorphous nature. FTIR analysis indicates dependence of the number of structural units of BO3 and BO4 on Bi2O3 concentration. It is assumed that Bi2O3 enters the structure in the form of BiO6. Bi2O3 in different structural units like tri, tetra, penta and octahedral groups are confirmed in the glass matrix. The change of density, molar volume and N4 ratio with Bi2O3 content confirm the transformation of structural units of BO3 into BO4 by Bi2O3 addition